2019
DOI: 10.1128/aac.02232-18
|View full text |Cite
|
Sign up to set email alerts
|

Isavuconazole in the Treatment of Coccidioidal Meningitis

Abstract: Patients with coccidioidal meningitis require lifelong antifungal therapy. Cumulative toxicity and lack of antifungal efficacy require salvage therapy in the treatment of some patients. In a retrospective review of nine patients with coccidioidal meningitis treated with isavuconazole, successful therapy was seen in three patients and stable disease was confirmed in six patients. Isavuconazole may be a useful addition to the therapeutic choices currently available for coccidioidal meningitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…If there is treatment failure, a serum fluconazole trough should be checked for therapeutic levels. Other azole options to treat active pulmonary coccidioidomycosis include itraconazole, voriconazole, posaconazole, or isavuconazole [ 36 , 37 ]. Notably, echinocandins have minimal activity against Coccidioides and should not be used as monotherapy for coccidioidomycosis.…”
Section: Discussionmentioning
confidence: 99%
“…If there is treatment failure, a serum fluconazole trough should be checked for therapeutic levels. Other azole options to treat active pulmonary coccidioidomycosis include itraconazole, voriconazole, posaconazole, or isavuconazole [ 36 , 37 ]. Notably, echinocandins have minimal activity against Coccidioides and should not be used as monotherapy for coccidioidomycosis.…”
Section: Discussionmentioning
confidence: 99%
“…Isavuconazole (ISAV), the active moiety of the triazole antifungal prodrug isavuconazonium sulfate (ISAVUSULF), has demonstrated potent in vitro activity against isolates of Coccidioides spp. Clinical studies in small cohorts of patients have reported good clinical outcomes with this triazole ( 6 , 7 ). Experimental models with Coccidioides spp.…”
Section: Textmentioning
confidence: 99%
“…After exclusion of reports published in non-English language or in which clinical and therapeutic data were not available for the purpose of the present review, a total of 41 cases have been included. Clinical and demographic characteristics, details of the antifungal treatment, outcome and adverse effects reported on these patients are summarized in Table 2 [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Thirty-three out of 42 (78.5%) patients were male and the mean age was 52 years (range 20–79).…”
Section: Isavuconazole In Non-hematological Patientsmentioning
confidence: 99%